RESPON UNI EROPA TERHADAP INVASI RUSIA DI UKRAINA TAHUN 2021-2022 - Charisya "; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The European Union is an entity that is very concerned about the implementation of human rights by countries in the world. Russia's invasion of Ukraine has led to violations of humanity, especially in Ukraine. The adverse impacts from a humanitarian, infrastructural and economic perspective prompted the author to examine how the European Union responds to human rights violations in Ukraine. To discuss the topic of responses to human rights violations that occurred, qualitative methods were used by collecting secondary data from books, journals, official publications of official government and non-government institutions, news from newspapers, or other reliable sources. The discussion uses the perspective of liberalism and diplomacy theory. The results of the study show that the European Union is very responsive in dealing with human rights violations in Ukraine. The policy of sanctions and invitations from the international community to punish or condemn Russia shows the European Union's serious determination. Handling victims affected within Ukraine by sending personnel and logistics in large numbers with a significant budget. German acceptance of nearly 1,055,323 Ukrainian refugees with very adequate facilities without hindrance from anti-refugee groups in Germany. The European Union is also providing €668 million in humanitarian aid to help civilians affected by the war in Ukraine.. Keywords: Invasion of Russia, Ukraine, European Union, Human Rights, Sanctions, Aid.